(untitled) (The Review of Diabetic Studies, 2024)
Background The value of various health information systems for managing the environment and the overall transformation of corporate structure brought about by the development of Health Information Systems (HIS) have become vital components in modernizing primary health care (PHC), aiming to enhance efficiency, accessibility, and quality of care. Despite the tremendous potential that information systems (IS) provide in supporting primary health care functioning, the design, development and implementation of these systems is a non-trivial task.. Nurses and family medicine physicians are integral to HIS implementation and utilization, contributing to patient-centered care, chronic disease management, and preventive health strategies. Additionally, technology has altered the information requirements and company structure. The introduction and application of information technologies (IT) in healthcare in our increasingly globalized society has been greatly aided by advancements in computer science and the growing need for communication. Despite these advantages, challenges such as system interoperability issues, inadequate training, Aim of the study: To assessment of the Health Information Systems on Improving Primary Health Care , role of Family Medicine physicians and Nursing in Health Management in Saudi Arabia 2024. Method: This is a cross-sectional study targeting health care workers in Saudi Arabia. Two validated questionnaires were used; the first validated questionnaire focuses on assessment Health Information Systems on Improving Primary Health Care and Role of Family Medicine physicians and Nursing. Results: the majority of participants age 40-49 years were (37.0%) regarding gender the majority of participant male were (58.0%) majority of participant health Family Medicine were (43.0%) Conclusion: Family Medicine physicians and Nursing professionals play pivotal roles in leveraging these systems, contributing to improved health outcomes through their active participation in patient-centered care and health management strategies. Integral to HIS implementation and utilization, contributing to patient-centered care, chronic disease management, and preventive health strategies . Despite these advantages, challenges such as system interoperability issues, inadequate training, and resistance to adoption often hinder effective integration.